Can adipokines serum levels be used as biomarkers of hand osteoarthritis?. (3rd April 2018) - Fioravanti, A.; Cheleschi, S.; De Palma, A.; Addimanda, O.; Mancarella, L.; Pignotti, E.; Pulsatelli, L.; Galeazzi, M.; Meliconi, R.
Abstract: Purpose: To evaluate serum levels of visfatin, resistin and adiponectin in patients with erosive (E) and non-erosive (NE) osteoarthritis (OA) of the hand (HOA) compared to normal controls (NC). Methods: 94 outpatients with E HOA and NE HOA and 21 NC were enrolled. The radiological assessment of both hands was performed according to the Kellgren–Lawrence and Kallman score. Patients were divided into two subsets (lone HOA or generalized OA) based on clinically OA involvement of knee and hip. Serum visfatin, resistin and adiponectin levels were determined by ELISA assay. Results: Visfatin was significantly higher in E HOA patients in comparison to NC and NE HOA group. Resistin showed a significant increase in both E HOA and NE HOA groups versus NC, in particular in generalized OA. No significant differences among groups were found in adiponectin. The Kallman score was more severe in the two subsets of E HOA patients compared to NE HOA. Conclusions: This study showed increased levels of resistin in erosive and non-erosive HOA, and higher visfatin levels in E HOA in comparison to NE HOA. These data suggest the adipokines possible role in the pathogenesis of HOA and their potential usefulness as biomarkers of the disease.